Management of Sodium Imbalance - Purwanto, Barkah Djaka; Perdana Putri, Rachma Greta (Ahmad Dahlan Medical Journal, 2024)
Sodium imbalance consists of hyponatremia and hypernatremia. Acute and severe hyponatremia and hypernatremia are life-threatening conditions. Rapid and slow correction should be considered for optimal outcomes, as aggressive management is often associated with the danger of demyelination and cerebral edema. This review aims to determine the safe management of sodium imbalance so that it is hoped that in overcoming critical conditions it does not transfer to other critical conditions that are equally fatal. The data search strategy uses the PubMed and Google Scholar databases between 2010 and 2022 with free full text that can be downloaded. The findings emphasize that acute and severe hyponatremia and hypernatremia are often life-threatening conditions. Management of these conditions requires caution, as aggressive correction in hyponatremia can result in osmotic demyelination, while hypernatremia can lead to cerebral edema. Despite theoretical risks, the study found no significant difference in 30-day mortality, seizures, cerebral edema, or decreased consciousness between fast and slow correction methods. The conclusion underscores the importance of tailored and cautious management strategies to mitigate the risks associated with sodium imbalance corrections.